SOLUSI KAMPANYE TERSELUBUNG DI HARI TENANG PEMILU - Fauzi, Agus Machfud (Metafora: Education, Social Sciences and Humanities Journal, 2015)
Quiet days is one of a series of elections be used as a policy in each of the Electoral Law (Legislative, President and Head of Region) in order to be a separation between the days of the campaign were at odds a little bit with the D-day implementation of the voting and counting. A quiet day at the time of the elections is an opportunity for electoral participants to rest after a long activity to meet constituents during the campaign schedule. Election participants are expected colling down after delivering a program, a vision and mission for the implementation of the campaign with a variety of creative shapes and models of the campaign. Voters as the object of the campaign as well as subjects that determine victory or defeat of election participants, given the opportunity to weigh up between the pair of candidates, that is where the best of the candidates who have offered programs, vision and mission during the campaign. Quiet day is expected to be the capital of preparation conscience of voters, still somewhat tainted by parties who are not responsible, either the presence of a covert campaign, black campaign, partisan survey implementation and violations of other quiet day.